Seasonal dynamics in bacterial communities of closed-cage broiler houses - Chen, Huan; Yan, Han; Xiu, Yan; Jiang, Linlin; Zhang, Jianlong; Chen, Guozhong; Yu, Xin; Zhu, Hongwei; Zhao, Xiaoyu; Li, Youzhi; Tang, Wenli; Zhang, Xingxiao (Frontiers in Veterinary Science, 2022)
The bacteria contained in air aerosols from poultry houses are closely connected to animal health and production. This study aimed to investigate the seasonal factors on microbial aerosol concentration, particle size and bacterial spectrum composition inside a closed-cage broiler house. Then, 16S rDNA sequencing technology was applied to analyze the characteristics of bacterial abundance and diversity. The results indicated that the concentration of bacterial aerosol in the broiler house varied significantly in different seasons, with a concentration range of 5.87～15.77×103 CFU/m3, and the highest and lowest concentrations in the summer and winter, respectively. Microbiological analysis showed that the proportion of Gram-negative bacteria in autumn was significantly higher than that in summer (P<0.05). In addition, the floral structure of potential pathogenic bacterial genera also differed by season. Escherichia-Shigella, Streptococcus, Acinetobacter, Pseudomonas were identified in the bacterial aerosols. Importantly, the relative abundance of Firmicutes in spring and autumn was much higher. In contrast, the relative abundance of Proteobacteria in spring and autumn was lower than that in summer and winter. Altogether, results revealed the effects of seasonal factors on the diversity and abundance of bacteria and the distribution characteristics of major opportunistic pathogens in the air of closed-cage broiler houses. These results will provide important information for exploring the potential risk of aerosols from poultry houses all four seasons.